Загальні методичні підходи до практичного запровадження релігієзнавчого компонента у сучасних школах Франції - Лаухіна, Інна (Studies in Comparative Education, 2014)
У статті йдеться про загальні методичні підходи до запровадження релігієзнавчого компонента знань змісту загальної середньої освіти Франції. Представлено огляд загальних методичних підходів щодо освітнього аспекту релігійних знань та їх виховний потенціал. Проаналізовано освітні програми з філологічних, суспільствознавчих, природно-математичних та естетичних дисциплін для французьких колежів і ліцеїв. Зроблено висновок про те, що при викладанні знань про релігію вчитель може поєднувати методики окремого предмета та метапідходи, які охоплюють усі навчальні дисципліни. В статье речь идет об общих методических подходах к реализации религиеведческого компонента знаний содержания общеобразовательной школы Франции. Представлен обзор общих методических подходов относительно познавательного аспекта знаний о религии и их воспитательного потенциала. Подан анализ учебных программ филологических, обществоведческих, естественно-математических и эстетических дисциплин для французских коллежей и лицеев. Сделан вывод о том, что учитель, преподавая знания о религии, может объединить методику отдельного предмета с метаподходами, которые охватывают все учебные предметы. The article describes general methodological approaches to the emplementing of religious component of knowledge of secondary school content in France. The description of general methodological approaches to the educational aspect of religious knowledge and their educational potential is presented. While implementing the religious component the logical idea is taken into consideration. Also the methodology of it’s conducting is of vital importance. Such methodological approaches are used as comparative, historical, policultural, investigating, and others. Educational programmes in philological, humanistic, scientific, mathematical and asthetic subjects in French colleges and high-schools. The realization of the main methodological approaches in religious education rquires much effort and a strong team of teachers, French educators mention. The module organization of the time-table is also necessary. The article dwells on French educational programmes for colleges and high-schools. They contain recommendations for the methods which should be used when conducting the subject. The programmes are legal documents for methodological support. But they also emphasize pedagogical art of the teacher who can use general methodological approaches. For the realization of the religious component they use the methods which can be applayed to any subject. There is a conclusion that when conducting religion the teacher can combine the methodology of a separate subject and approaches which include all subjects.